Quantitative Analysis of Socio-Economic Determinants, Mother-in-Law Dynamics, and Dowry Practices in Domestic Violence against Women in Punjab, Pakistan - Sadaf Sarwar; Dr. Muhammad Iqbal Zafar* (Journal of Religion and Society, 2025)
The purpose of this study is to explore both the social/cultural factors that influence or lead to domestic violence against women (DVAW), and the consequences that arise from it in the province of Punjab, Pakistan. This research identifies DVAW within a broader multi-faceted conceptualization of structural inequality, patriarchal family structure and psychosocial dynamics; and acknowledges that DVAW represents a chronic public health and human rights issue. In the quantitative approach a cross sectional survey was conducted to collect data from 600 married women of aged 18 to 49 years from three Districts of Punjab, namely Faisalabad, Lahore and Gujranwala. Multistage random sampling was used for the selection of the 600 respondents. The sampling based upon four stages, Districts, Tehsils, Union Councils and the respondents. At each stage, random sampling was used to ensure the scope of the study findings and generalization. Quantitative data were analyzed using descriptive, inferential and multivariate to assess the effect of socio-economic and demographics such as education level, age of the respondent, income of the family and number of children on domestic violence. The findings indicate that domestic violence is caused by culturally held attitudes toward gender roles, family honor, and male dominance. Also, the study found that income of the family, respondents’ education, and age at marriage, number of children, family income, dowry practices and mother-in-law attitude dynamics are the contributing factors of domestic violence against women. The effects of this type of violence are very negative and include social isolation, emotional distress, physical injury, and worsened mental health. Although there are laws in place, the participants were unaware of their rights as women, how to seek help, etc. The study emphasizes the need for culturally appropriate intervention strategies that challenge gender stereotypes, increase women’s autonomy, and provide psychosocial support through policy and practice. There should be counseling at community level for the men for overcoming their issues and psychological problems i.e., emotional dysregulation, low self-esteem, and aggression, to overcome their perpetuation of violence. There is a dire need of personality screening and counseling of the partners to make them aware about the violence against women. On the other hand, it is also required for better adjustment of both the partners. Keywords: Domestic violence, dowry practices, mother-in-law attitude, social isolation, society and acceptance, emotional distress, physical injury, health, Punjab, Pakistan.